THE EFFECT OF DISCIPLINE AND PROFITABILIAS POLICY ON WORK RESULTS AT PT PULAHAN SERUWAI - Azlansyah Putra (Ikatan Dosen Menulis, 2025)
Discipline and profitability are important aspects to achieve a result. Many results from discipline and profitability if all are implemented properly and will produce work achievements that are the goals. The purpose of this writing is to analyze and determine the influence of discipline and profitability on work results at PT Pulahan Seruwai Kec Air Batu Kab Asahan. The results of the SPPSS 16 analysis of the questionnaire data on Discipline and profitability on Work Results at PT Pulahan Seruwai Kec Air Batu Kab Asahan are (1) partially the Discipline variable affects the Work Results of workers at PT Pulahan Seruwai Kec Air Batu Kab Asahan, (2) partially the profitability variable affects the Work Results of workers at PT Pulahan Seruwai Kec Air Batu Kab Asahan, (3) simultaneously there is a positive and significant influence between the Discipline and profitability variables on Work Results on workers at PT Pulahan Seruwai Kec Air Batu Kab Asahan.